Faktor-Faktor yang Mempengaruhi Contract Change Order pada Pekerjaan Rehabilitasi Jalan Mataiwoi-Abuki - Rajanun, Rajanun; Lakawa, Irwan; Hawa, Sitti; Haryono, Haryono; Sufrianto, Sufrianto (Sultra Civil Engineering Journal (SCiEJ), 2022)
The research was conducted using descriptive statistical methods, namely by analyzing data and questionnaires to determine the mean and then calculating the value of the Relative Interest Index (IKR). This analytical method will be very useful for identifying the rank of respondents and giving priority to study variables. The results showed that the factors causing CCO were the effect of cost (0.362) with a t count of 0.869. The dominant factors causing Contract Change Order (CCO) that affect cost and time are the contractor factor, then the influence of cost, natural conditions, planning & design, time, and the lowest one is the owner's influence.